External dose-rate measurements based on smartphone CMOS sensors. (September 2020) - Mafodda, Alessia; Woda, Clemens
Abstract: In the framework of the European Project CONFIDENCE („COping with uNcertainties For Improved modelling and DEcision making in Nuclear emergenCiEs"), the characterization of two applications ("RadioactivityCounter and "GammaPix") that enable dose-rate measurements with an ordinary smartphone was carried out. In case of a nuclear emergency, such softwares allow to use the CMOS sensor of the built-in camera as a radiation detector. This paper presents the results of the scientific investigation on the reliability of the so-called "citizen measurements" performed with 14 different mobile phones chosen among the most common brands sold in 2017. All tests were carried out at room temperature and in different reference fields at the Secondary Standard Dosimetry Laboratory of the Helmholtz Zentrum München. Investigated properties were the response at different dose-rate levels, influence of integration time, background, energy dependence and angular dependence. Highlights: Smartphone CMOS sensors of the built-in cameras allow dose-rates measurements through dedicated applications. Characterization of two main applications is provided for 14 different phone models. Smartphones can identify areas of high radioactive contamination but their reliability at natural radioactivity level is difficult to assess.